An interprofessional exploration of nursing and social work roles when working jointly with families - Bennett, Elaine; Hauck, Yvonne; Radford, G.; Bindahneem, S. (Informa Healthcare, 2016)
Ngala, an early parenting not-for-profit organisation in Western Australia, has provided services to families with young children since 1890. Child health nurses and mothercraft nurses were the primary workforce until the 1980s when a social worker was employed and a new era of interprofessional collaboration began. Evidence to date has focused on nursing workforce, interprofessional education, and interprofessional teams. Little is known about the roles of nursing and social work when working jointly with families. A new service commenced in 2012 for families with children with developmental delays. Social workers and child health nurses were employed for this service model. Our study aim was to explore the perceptions of how nurses and social workers work together with a family providing psychosocial support across a new service. The study was conducted alongside implementation of this new service. An exploratory case study approach was adopted to generate an in-depth understanding of the roles of nurses and social workers. In total, 22 semi-structured interviews and one focus group across the first year of implementing the new service were undertaken. Analysis of these data revealed four major themes. Findings presented in this article will inform further reflection and consideration into the future interprofessional workforce priorities and requirements for Early Parenting Services.